Photographer - Waller T; South Africa; Nafte Debbie
An introduction to the job of Photographer, describing the work of a Photographer, the skills and personal qualities required, school subjects that are helpful, and the training and opportunities that are available. the book can help learners to decide if this is a suitable career for them.
Junior Non-Fiction-; Juvenile Literature